Intranasal Administration of Insulin Reduces Chronic Behavioral Abnormality and Neuronal Apoptosis Induced by General Anesthesia in Neonatal Mice - Li, Hengchang; Dai, Chun-ling; Gu, Jin-Hua; Peng, Shengwei; Li, Jian; Yu, Qian; Iqbal, Khalid; Liu, Fei; Gong, Cheng-Xin (Frontiers in Neuroscience, 2019)
Children, after multiple exposures to general anesthesia, appear to be at an increased risk of developing learning disabilities. Almost all general anesthetics, including sevoflurane that is commonly used for children, are potentially neurotoxic to the developing brain. Anesthesia exposure during development might also associate with behavioral deficiencies later in life. To date, there is no treatment to prevent the anesthesia-induced neurotoxicity and behavioral changes. In this study, we anesthetized 7-day-old neonatal mice with sevoflurane for 3 hrs per day for three consecutive days and found that the anesthesia led to mild behavioral abnormalities later in life that were detectable by using novel object recognition test, Morris water maze, and fear conditioning test. Biochemical and immunohistochemical studies indicate that anesthesia induced a decrease in brain level of postsynaptic density 95 (PSD95), a postsynaptic marker, and marked activation of neuronal apoptosis in neonatal mice. Importantly, insulin administered through intranasal delivery prior to anesthesia was found to prevent the anesthesia-induced long-term behavioral abnormalities, reduction of PSD95, and activation of neuronal apoptosis. These findings suggest that intranasal insulin administration could be an effective approach to prevent the increased risk of neurotoxicity and chronic damage caused by anesthesia to the developing brain.